2021
DOI: 10.3389/fcomm.2021.689470
|View full text |Cite
|
Sign up to set email alerts
|

L2 Processing of Words Containing English /æ/-/ɛ/ and /l/-/ɹ/ Contrasts, and the Uses and Limits of the Auditory Lexical Decision Task for Understanding the Locus of Difficulty

Abstract: Second language (L2) learners often exhibit difficulty perceiving novel phonological contrasts and/or using them to distinguish similar-sounding words. The auditory lexical decision (LD) task has emerged as a promising method to elicit the asymmetries in lexical processing performance that help to identify the locus of learners’ difficulty. However, LD tasks have been implemented and interpreted variably in the literature, complicating their utility in distinguishing between cases where learners’ difficulty li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…L2 learners need to overcome the influence of L1 in developing the L2 phonological system and new form-meaning mappings for L2 LRs. The specific difficulties in L2 lexical encoding of both form and meaning can often be traced to a particular combination of L1 and L2 ( Jarvis, 2000 ; Barrios and Hayes-Harb, 2020 , 2021 ; Llompart, 2021 ). For example, an L1 German speaker may not encode the difference in the English words cod and cot due to final consonant devoicing in German, while encoding this difference will not present a problem to an L1 French speaker.…”
Section: Is the Construct Of Flr New Or Does It Rename The Existing Constructs?mentioning
confidence: 99%
See 1 more Smart Citation
“…L2 learners need to overcome the influence of L1 in developing the L2 phonological system and new form-meaning mappings for L2 LRs. The specific difficulties in L2 lexical encoding of both form and meaning can often be traced to a particular combination of L1 and L2 ( Jarvis, 2000 ; Barrios and Hayes-Harb, 2020 , 2021 ; Llompart, 2021 ). For example, an L1 German speaker may not encode the difference in the English words cod and cot due to final consonant devoicing in German, while encoding this difference will not present a problem to an L1 French speaker.…”
Section: Is the Construct Of Flr New Or Does It Rename The Existing Constructs?mentioning
confidence: 99%
“…An ERP study of N400 effects for phonologically confusable incongruent lexical substitutions and the role of different factors contributing to the lack of sensitivity of L2 speakers to such substitutions will test the role of FLRs in sentence processing. Additionally, different dimensions of fuzziness of LRs can be further explored by comparing the performance of multiple native language groups on multiple phonological contrasts (similar to the approach of Barrios and Hayes-Harb, 2021 ). Word training studies can manipulate the hypothesized degree of fuzziness for L2 words (e.g., based on phonological contrasts or L1 transfer predictions) to examine how FLRs change over time and what consequences fuzziness has for their long-term maintenance in memory.…”
Section: Final Remarksmentioning
confidence: 99%
“…Based on the observed disassociation between phonetic categorization and lexical encoding, the authors suggested that the problems experienced by L2 speakers in auditory word recognition stemmed from phonolexical encoding in addition to phonetic discrimination and categorization. Using an auditory lexical decision task to locate learners' difficulty, Barrios and Hayes-Harb (2021) observed contrastive accuracy patterns for the English /l/-/ɹ/ contrast (e.g., "[l]ecture," "[ɹ]ecture"). Native English speakers showed highly accurate and symmetric classification for words and pseudowords (interpreted as indicative of precise perceptual and lexical encoding), Chinese L2 learners exhibited higher accuracy for [l] words and [l] pseudowords (interpreted as perceptual coding difficulty), and the Korean L2 learners exhibited more accurate performance for [l] for words and [ɹ] for pseudowords (interpreted as lexical encoding difficulty).…”
Section: Background Literaturementioning
confidence: 99%
“…Spoken word recognition in a second language (L2) is not always successful and effortless, with recent years witnessing a growing interest in understanding how L2 spoken words are perceived, encoded, and accessed (e.g., Barrios & Hayes-Harb, 2021;Cutler et al, 2006;Darcy et al, 2012Darcy et al, , 2013Escudero et al, 2008Escudero et al, , 2014Llompart, 2021). Adult L2 learners are sensitive to the phonological contrasts in their first language (L1), whereas they experience difficulties in discriminating novel L2 contrasts (Best, 1995;Best & Tyler, 2007;Flege, 1995;Flege & MacKay, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, "fuzziness" has been used to describe the phonolexical representation of novel phonological categories that are effectively ambiguous due to overlap with familiar (native) categories. In these cases, the learner maintains a phono-lexical contrast via the relative fuzziness of the new and familiar phonemes, resulting in asymmetric lexical activation because fuzzier representations are contacted by a wider range of acoustic events than are less fuzzy representations (as in scenarios reported by e.g., Barrios & Hayes-Harb, 2021;Darcy, Daidone & Kojima, 2013;Escudero, Hayes-Harb & Mitterer, 2008;Weber & Cutler, 2004). In other cases, learners' phono-lexical representations are not inexact or ambiguous, but rather neutralize a novel contrast to the familiar category.…”
mentioning
confidence: 99%